2000
DOI: 10.1080/136828200247133
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and natural history of primary speech and language delay: findings from a systematic review of the literature

Abstract: The prevalence and the natural history of primary speech and language delays were two of four domains covered in a systematic review of the literature related to screening for speech and language delay carried out for the NHS in the UK. The structure and process of the full literature review is introduced and criteria for inclusion in the two domains are specified. The resulting data set gave 16 prevalence estimates generated from 21 publications and 12 natural history studies generated from 18 publications. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
87
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 476 publications
(90 citation statements)
references
References 56 publications
3
87
0
Order By: Relevance
“…Several studies have estimated the prevalence of communication disorders in children to be between 2% and 25% (Law, Boyle, Harris, Harkness, & Nye, 2000;McLeod & Harrison, 2009;Tomblin et al, 1997). Based on these prevalence rates alone, it is clear that communication disorders are a relatively common problem of childhood that must be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have estimated the prevalence of communication disorders in children to be between 2% and 25% (Law, Boyle, Harris, Harkness, & Nye, 2000;McLeod & Harrison, 2009;Tomblin et al, 1997). Based on these prevalence rates alone, it is clear that communication disorders are a relatively common problem of childhood that must be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Law et al [8] concluded that difficulties persist without intervention, and thus, it is important to assess the effectiveness of a specific intervention programme for these children.…”
Section: Introductionmentioning
confidence: 99%
“…These language skills assessed by TL-ALPE are well documented in the scientific literature concerning language development, language disorders and psycholinguistics [1,19,21]. …”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of language delay and disorders ranges from 1 to 15% according to a systematic review of the literature [1]. Language assessment of preschool children with developmental language disorders is typically performed with standardized tests in combination with other information [2].…”
Section: Introductionmentioning
confidence: 99%